Isolation, Partial Purification and Characterization of Molybdenum-Reducing Enzymes from an Antartica Bacterium (Gamma-Proteobacterium Strain Dr.Y1) - Ahmad, Siti Aqlima (2006)
Bacterial Isolate no. J7A was isolated from Jubany Station, Antarctica and it has the capability to reduce the heavy metal molybdenum (molybdate) to molybdenum blue in a solid medium agar, pH 7 at 10°C, after for 4 days of incubation. Isolate J7A was identified as Gram-negative and gamma-Proteobacterium Strain Dr.Y1 through moleculare phylogenetics analysis of the sequenced 16s rRNA gene. The optimization studies were carried out to optimize the production of molybdenum blue. The combination of 1% (w/v) glucose, 0.3% (w/v) ammonium sulphate, 0.1% (w/v) of yeast extract, 30mM molybdate, and low phosphate medium at pH 7 give the optimum production of Molybdenum blue. Partial purification and characterization were conducted on molybdenum reducing enzyme with anion exchange chromatography using Macro-Prep High-QTM column and gel filtration chromatography using Agilent ZorbaxTM (GF-250) column. Three bands were visualized on the gel filtration fraction at 39, 36 and 33 kDa using the SDS polyacrylamide-gel electrophoresis (SDS-PAGE) suggesting that purification was not achieved. In enzyme kinetic studies, NADH serves as the substrate for electron donor and 12-MP act as the substrate for electron acceptor. The Km and Vmax for NADH were 0.4838 mM and 21.51 units/mg enzyme respectively. While the values for 12-MP were 5.347 mM and 64.04 units/mg enzyme respectively. The characterization of Mo-reducing enzyme studies were carried out at the optimum pH of 7.5 using 50mM Tris-HCl at 15°C. The enzyme is stable at -20°C for six days in Tris-HCL buffer at pH 7.5.